Electron irradiation effects on Vickers hardness of potassium-based geopolymers: the role of water content - Do, Thi-Mai-Dung; Yaru, Yang; Kikuchi, Takashi; Nakayama, Tadachika; Thorogood, Gordon James; Suematsu, Hisayuki (Frontiers in Nuclear Engineering, 2025)
Potassium-based geopolymers were synthesized with varying initial water content (7–10 mol %). Samples were initially cured under tight-lidded conditions at different temperatures (room temperature, 40 °C, and 60 °C) for the initial 24 h and then transitioned to ambient curing without lid. Analysis of the pore size distribution revealed that higher initial water content generally led to larger pores, while higher curing temperatures resulted in smaller pores. Vickers hardness measurements showed a dependence on both initial water content and curing temperature. The electron beam irradiation was processed up to 16 kGy by pulsed linear electron accelerator at Nagaoka University of Technology and up to 992 kGy by electron beam irradiation at the Takasaki Institute of Advanced Quantum Science. The Vickers hardness of a selected sample remained largely unchanged even after electron beam irradiation up to a high dose.